2017
DOI: 10.1371/journal.pone.0169992
|View full text |Cite
|
Sign up to set email alerts
|

Complete Chloroplast Genomes of Erianthus arundinaceus and Miscanthus sinensis: Comparative Genomics and Evolution of the Saccharum Complex

Abstract: The genera Erianthus and Miscanthus, both members of the Saccharum complex, are of interest as potential resources for sugarcane improvement and as bioenergy crops. Recent studies have mainly focused on the conservation and use of wild accessions of these genera as breeding materials. However, the sequence data are limited, which hampers the studies of phylogenetic relationships, population structure, and evolution of these grasses. Here, we determined the complete chloroplast genome sequences of Erianthus aru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
26
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 70 publications
3
26
1
Order By: Relevance
“…The next clade is bounded by Miscanthus olygostachyus at its root. Interestingly, this species is sister to Miscanthus sinensis var Purpurascens and two previously published sequences of M. sinensis and Miscanthus floridulus (Lloyd Evans and Joshi 2016;Nah et al 2016;Tsuruta et al 2017). This would indicate that the M. sinensis forms have either been misidentified or they represent hybrids of M. oligostachyus with M. sinensis.…”
Section: Discussionsupporting
confidence: 55%
“…The next clade is bounded by Miscanthus olygostachyus at its root. Interestingly, this species is sister to Miscanthus sinensis var Purpurascens and two previously published sequences of M. sinensis and Miscanthus floridulus (Lloyd Evans and Joshi 2016;Nah et al 2016;Tsuruta et al 2017). This would indicate that the M. sinensis forms have either been misidentified or they represent hybrids of M. oligostachyus with M. sinensis.…”
Section: Discussionsupporting
confidence: 55%
“…Sun & al., ; Duvall & al., ; Zhang & al., ; Medina & al., ; Saarela & al., ; Yan & al., ). Several plastome phylogenomic analyses in Andropogoneae have also successfully recovered evolutionary relationships among taxa, helping to define their taxonomic circumscriptions (Evans & Joshi, ; Welker & al., ; Arthan & al., ; Tsuruta & al., ). The phylogenomic investigation of Arthan & al.…”
Section: Introductionmentioning
confidence: 97%
“…The analysis of Tsuruta & al. (), based on 76 plastid genes, showed that Saccharum officinarum is more closely related to Miscanthus sinensis Andersson than to Erianthus arundinaceus (Retz.) Jeswiet.…”
Section: Introductionmentioning
confidence: 99%
“…Molecular genetics studies indicate that Miscanthus and Saccharum are closely related (Amalraj & Balasundaram, 2006;Sacks, Juvik, Lin, Stewart, & Yamada, 2013;Sobral, Braga, LaHood, & Keim, 1994). The two genera were estimated to have separated from a common ancestor about 3.64 mya (Tsuruta, Ebina, Kobayashi, & Takahashi, 2017). Moreover, intergeneric hybrids of Saccharum and Miscanthus have been bred previously, and these intergeneric hybrids are often termed miscanes.…”
Section: Introductionmentioning
confidence: 99%